USULAN PENGELOLAAN DIVISI TEKNOLOGI INFORMASI PT CHAROEN POKPHAND INDONESIA TBK. DENGAN METODE NEW INFORMATION ECONOMICS - Hudiarto, Hudiarto; Wibowo, Chandra; Halim, Agus Prima (CommIT (Communication and Information Technology) Journal, 2007)
Charoen Pokphand Indonesia company was a big cattle food company and the distribution spread all overIndonesia. In this research, it was proposed to analyse the use of information technology investment and how to run thedivison budget using New Information Economics (NIE) method and using four out of five NIE practice, which are ategicDemand/ Supply Planning, Innovation, Prioritization, and Alignment. The research result was the company managementwill be able to know which Information System (IS) and Information Technology (IT) that was more important to bedeveloped also which one was not because did not give positive impact. So, the IT division can alocate the IS and ITinvestment on project that only support the company performance.Keywords: new information economics, investment, project, information technology, information system